Tarihten günümüze kadar Bereketli Hilal’de sosyo-ekonomik yapı - Ötümlü, Arzu (My University, 2006)
(ÖZET) İnsanlık tarihinin önemli dönüm noktalarının yaşandığı Dicle ve Fırat havzalarını oluşturan Mezopotamya topraklarına Amerikalı antropolog James Henry Breasted tarafından “Bereketli Hilâl” adı verilmiştir. Tarımın doğuşu, yerleşik hayata geçiş, yazının icadı, Kent devrimi gibi gelişmelerin yaşandığı bölge aynı zamanda üç büyük dinin doğduğu topraklar olarak tarih sahnesindeki önemini her daim korumuştur. Bereketli Hilâl zaman içerisinde gelişimini sürdürmüş, ihtiyaçların doğurduğu tetikleyici unsurlarla da ekonomik ve siyasal oluşumun ilk gözlendiği bölge olmuştur. Modern çağa geçiş sürecinde Bereketli Hilâl üzerinde Sümerler, Akadlar, Hurriler, İsin ve Larsa Krallıkları, Amurrular, Asur ve Bâbil gibi medeniyetler doğmuştur. Bu medeniyetlerin oluşmasında ve sürmesinde askeri, dini ve ekonomik yapılaşma büyük önem taşımaktadır. Toplumsal sınıflaşma, dini unsurlar ve ticaretin artması ise toprak mücadelelerinin başlamasına zemin hazırlamıştır. Bölgede kurulan uygarlıklar gerek birbirleriyle gerekse başka bölgelerden gelen istilalarla sık sık hakimiyet değişikliğine uğramışlardır. Bu durum Bereketli Hilâl’in Osmanlı İmparatorluğu himayesine girmesine kadar sürmüştür. Ancak Birinci Dünya Savaşı sonrası bölge İngiltere ve Fransa’nın manda yönetimine girmiştir. Daha önce Suriye topraklarına dahil olan Filistin, Ürdün ve Lübnan bağımsız devletler olarak varlıklarını sürdürmüşlerdir. Neticede bir sömürge ekonomisine sahip olmaları ciddi zorluklar yaşamalarına sebep olmuştur. Filistin 1948’de İsrail devletinin kurulmasıyla bağımsızlığını yitirmiştir. Diktatörlük rejimi altında bulunan Irak’ın ise ABD tarafından işgaliyle söz konusu olabilecek bir ekonomisi dahi kalmamıştır. Bereketli Hilâl geçmişten günümüze kadar etnik, dini ve ekonomik çatışmaların merkezi olmuştur. Bu unsurların bölgenin geleceğini şekillendirmesi ise kaçınılmaz bir gerçektir. SOCIO-ECONOMICAL STRUCTURE IN THE FERTILE CRESCENT FROM PAST UP-TO-DATE

The soil of Mesopotamia, constituting the river basins of the Euphrates and Tigris rivers, where the most important periods and crossroads of humanity were lived, was named as “the Fertile Crescent” by the American Anthropologist James Henry Breasted. This piece of soil has always preserved its importance in the history of humanity as the soil in which three major religions have arisen, agriculture has started, settled life has commenced, scripture was discovered and developments such as urban revolution were lived. The Fertile Crescent continued its development in time and has been the region where economic and political establishments have first taken place along with the triggering components, which came into existence as a consequence of needs. Kingdoms of Sumeria, Akad, Hurri, Isin and Larsa as well as civilizations such as Amurrus, Assyrians and Babylon were established on this land. Military, religious and economic structuring play a significant role in the formation and continuation of these civilizations. Social classes, religious components and increase of trade on the other hand have prepared the basis for beginning of struggles for soil. The civilizations established in the region have undergone changes of domination as a consequence of invasions from other regions and struggles among themselves. This continued until the rise of the Ottoman Empire in the Fertile Crescent. However, the region was under the dominance of mandate administration of England and France after the First World War. Palestine, Jordan and Lebanon that used to belong to Syria before continued their existence as independent countries. The fact that they experience the economy of colony state led to significant difficulties. Palestine lost its independence following the establishment of the state of Israel in 1948. Iraq, which had been a regime of dictatorship, does not have any economy now following the invasion of US. The Fertile Crescent had been the center of ethnic, religious and economic clashes from past until date. The shaping of the future of the region with these components is an undeniable reality. ESSENCE The social and economic structure of the land of Mesopotamia referred to as the “Fertile Crescent” by historians, the significance of which for humanity had been proven to a significant extent, had been mentioned. The cultural, political and economic structures of the civilizations and states on the region of “Fertile Crescent” covering a large part of the Middle East has been analyzed with a general approach.
Keywords: Mezopotamya_Ekonomik Durum; Mezopotamya_Sosyal Durum; Mezopotamya_Tarih; Orta Doğu_Tarih